2010
DOI: 10.1016/j.jalz.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative assessment of surrogate consent in dementia research

Abstract: Background-Research involving incapacitated persons with dementia involves complex scientific, legal, and ethical issues, making traditional surveys of layperson views regarding the ethics of such research challenging. We therefore assessed the impact of democratic deliberation (DD)-involving balanced, detailed education and peer deliberation-on the views of those responsible for persons with dementia.Methods-178 community-recruited caregivers or primary decision-makers for persons with dementia were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…For example, follow-up is needed on our findings that suggest disclosure of certain NWIs pertaining to issues of trust and fairness (i.e., commercial profits and insurance risk assessment) are of more concern to donors than other historically controversial issues (e.g., reproductive research). One way this could be accomplished is through engaging the public in a democratic deliberation to ascertain their preferences (Kim et al, 2011; Kim et al, 2010; Kim, Wall, Stanczyk, & De Vries, 2009) regarding policy options to determine how to best address the NWIs of biobank donors. Finally, a more representative national survey to assess public attitudes and preferences about NWIs is needed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, follow-up is needed on our findings that suggest disclosure of certain NWIs pertaining to issues of trust and fairness (i.e., commercial profits and insurance risk assessment) are of more concern to donors than other historically controversial issues (e.g., reproductive research). One way this could be accomplished is through engaging the public in a democratic deliberation to ascertain their preferences (Kim et al, 2011; Kim et al, 2010; Kim, Wall, Stanczyk, & De Vries, 2009) regarding policy options to determine how to best address the NWIs of biobank donors. Finally, a more representative national survey to assess public attitudes and preferences about NWIs is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previous study of caregivers of patients with AD using similar DD methods. 18 Third, these changes in attitude appear to be the effect of the deliberative process rather than simply of additional knowledge. Although the education group showed similar shifts in knowledge as the DD group, there was little change in their attitudes regarding surrogate consent.…”
Section: Rd Small Group Sessionmentioning
confidence: 98%
“…This ratio was based on a previous study 18 and a pilot study that estimated the no-show rate in the group assigned to DD, with the goal of achieving approximately similar numbers of respondents in each group. As described below, the DD group attended an all-day education and deliberation session.…”
Section: Participants Members Of the General Public (ն50 Years Old)mentioning
confidence: 99%
See 1 more Smart Citation
“…(1214, 26) Among our participants, we found that the older general public strongly supports a policy of surrogate consent for dementia research and that this support increased after in-depth education and peer deliberation; for example, at baseline, support for a policy of surrogate consent for a dementia research protocol involving gene transfer neurosurgery increased from 56% to 68% after deliberation. (22) Our thematic analysis of participants’ deliberations provides important insights into what this overall support means.…”
Section: Discussionmentioning
confidence: 85%